2007
DOI: 10.3139/217.2047
|View full text |Cite
|
Sign up to set email alerts
|

Constant Temperature Microfeature Embossing with Slowly Crystallizing Polymers

Abstract: A new microfeature embossing method utilizing a slowly crystallizing mechanism was investigated to eliminate thermal cycling, as needed in standard hot embossing. Poly(ethylene terephthalate) was used as a model system for demonstration. Due to its slow crystallization, amorphous PET film can be made by melt casting onto a chilled roll. The resulting amorphous film was embossed at a constant temperature of 180°C for a period of time comparable to or longer than the polymer's half-time of crystallization. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In theory, any materials (not necessarily a thermoplastic) that can be softened and solidified during processing can be used in embossing. Rather than using solvents or a chemical curing process, Yao et al (2007a) have investigated the feasibility of utilizing the unique property of slowly crystallizing polymers for achieving constant-temperature embossing. The recently developed solvent-assisted embossing method (Khang and Lee, 2000;Wang et al, 2005) may be considered as a specific method falling into this category.…”
Section: Constant-temperature Embossingmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, any materials (not necessarily a thermoplastic) that can be softened and solidified during processing can be used in embossing. Rather than using solvents or a chemical curing process, Yao et al (2007a) have investigated the feasibility of utilizing the unique property of slowly crystallizing polymers for achieving constant-temperature embossing. The recently developed solvent-assisted embossing method (Khang and Lee, 2000;Wang et al, 2005) may be considered as a specific method falling into this category.…”
Section: Constant-temperature Embossingmentioning
confidence: 99%
“…In addition, other softening and/or solidification processes, including solvent-assisted plastication (Khang and Lee, 2000;Wang et al, 2005) and isothermal softening and solidification of a slowly crystallizing polymer (Yao et al, 2007a), have also been reported in micromolding applications. In some cases, radiation-based curing methods are more useful.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors in a technical communication have conceptualized a new method for constant‐temperature embossing using supercooled amorphous polymers as embossing polymers. Slowly crystallizing polymers such as PET and PEEK can be quenched during melt processing to produce amorphous films with reasonable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%